Individual and Network Factors Associated With Racial Disparities in HIV Among Young Men Who Have Sex With Men: Results From the RADAR Cohort Study. (1st January 2019) - Mustanski, Brian; Morgan, Ethan; D'Aquila, Richard; Birkett, Michelle; Janulis, Patrick; Newcomb, Michael E.
Abstract : Background: Individual sexual risk behaviors have failed to explain the observed racial disparity in HIV acquisition. To increase understanding of potential drivers in disparities, we assessed differences across individual, network, and social determinants. Methods: Data come from RADAR (N = 1015), a longitudinal cohort study of multilevel HIV-risk factors among young men who have sex with men (YMSM) aged 16–29 years in Chicago, IL. Data collection includes biological specimens; network data, including detailed information about social, sexual, and drug-use networks; and psychosocial characteristics of YMSM. Results: Compared to white YMSM (24.8%) and Hispanic YMSM (30.0%), black YMSM (33.9%) had a higher prevalence of both HIV (32%; P < 0.001) and rectal sexually transmitted infections (26.5%; P = 0.011) with no observed differences in pre-exposure prophylaxis use. Black YMSM reported lower rates of sexual risk behaviors and more lifetime HIV tests ( P < 0.001) compared with all other YMSM; however, they were also significantly less likely to achieve viral suppression ( P = 0.01). Black YMSM reported the highest rate of cannabis use ( P = 0.03) as well as greater levels of stigma ( P < 0.001), victimization ( P = 0.04), trauma ( P < 0.001), and childhood sexual abuse ( P < 0.001). White YMSM reported higher rates of depression ( P < 0.001) and alcohol use ( P < 0.001). In network analyses, significant differences existed across network characteristics with black YMSM having the lowest transitivity ( P = 0.002), the highest density ( P < 0.001), and the highest homophily ( P < 0.001). Conclusions: Black YMSM do not report higher rates of HIV-risk behaviors, but social and network determinants are aligned toward increased HIV risk. These results suggest that network interventions and those addressing social determinants may help reduce disparities.